The Influence of Competence and Non-Work Environment on Loyality Mediated by Job Satisfaction and Employee Engagement - Trisninawati Trisninawati; Sunda Ariana; Sulaiman Helmi (Integrated Journal of Business and Economics (IJBE), 2023)
Understanding the intricate interplay between competence, non-work environment, job satisfaction, and employee engagement is imperative for optimizing employee loyalty and informing effective organizational strategies. This study aims to analyze the influence of competence and the environment outside the workplace on employee loyalty by considering the role of mediators in job satisfaction and employee engagement. This research method involves a survey of employees of Semen Baturaja Palembang Limited Liability Company in all regions of Palembang selected by convenience sampling technique. In this study, various interesting findings were obtained that can be understood in view of the various interrelated variables within the company, namely the significant positive effect of competence on job satisfaction, the positive effect of job satisfaction on employee engagement, and the positive influence of employee involvement on loyalty. This finding is also further confirmed by job satisfaction as a mediator of competency and work involvement variables, so companies, if they want employee involvement in the company, must first increase employee job satisfaction, which will then have an impact on employee loyalty itself